Land Use Dynamics and Ecological Effects of Photovoltaic Development in Xinjiang: A Remote Sensing and Geospatial Analysis - Babierjiang Dilixiati; Hongwei Wang; Lichun Gong; Jianxin Wei; Cheng Lei; Lingzhi Dang; Xinyuan Zhang; Wen Gu; Huanjun Zhang; Jiayue Zhang (Land)
As an important part of the emerging energy portfolio, the coordinated development of the photovoltaic (PV) industry and ecological environment is a core factor in realizing the high-quality development of the energy industry. Xinjiang, located in northwestern China, possesses vast open land, abundant solar radiation, and low land-use conflict, making it a strategic hub for large-scale PV power station deployment. However, the region’s fragile ecological background is highly sensitive to land-use changes induced by PV infrastructure expansion. Therefore, scientifically evaluating the ecological impacts of PV construction is essential to support environmentally informed operation and maintenance (O&M) strategies.This study investigates the spatial distribution of PV installations and their macro-scale ecological effects across Xinjiang from 2000 to 2020. Utilizing multi-temporal satellite remote sensing data and geospatial analysis techniques on the Google Earth Engine (GEE) platform, we constructed a Remote Sensing Ecological Index (RSEI) model to quantify the long-term ecological response to PV development. It was found that PV installations were concentrated in unutilized land (37.10%) and grassland (34.45%), with the smallest proportion being found in forested land (1.68%). Nearly 70% of the PV areas showed an improving trend in the ecological environment index, and there were significantly more ecological quality-improving areas than degraded areas (69% vs. 31%). There were significant regional differences, and the highest ecological environment index was found in 2020 for the Northern Xinjiang Altay PV area (0.30), while the lowest (0.10) was observed in Hetian in southern Xinjiang. The results of this study provide a spatial optimization basis for the integration of PV development and ecological protection in Xinjiang and provide practical guidance to help the government to formulate a comprehensive management strategy of “PV + ecology”, which will help to realize the synergistic development of clean energy development and ecological safety.